The effect of sugar content in flowers of cytoplasmic male sterile lines on hybrid seed production of upland cotton (Gossypium hirsutum) - WANG Xue-de; ZHAO Xiang-qian (浙江大学学报. 农业与生命科学版)
Soluble total sugar, sucrose and fructose content in petal, anther, stigma, nectary, bract and leaf of cytoplasmic male sterile lines, maintainer, restorer and hybrid F1 were determined respectively. The relationship between the visit frequency of honeybee and the yield of hybrid seed was analyzed. The soluble total sugar and sucrose content in petal, bract and nectary of male sterile line are significantly higher than in those of restorer, maintainer and hybrid F1, but the difference of fructose content among them is not noticeable. Sucrose content in flowers of male sterile lines is a key factor that effects on the bee visit frequency. Breeding male sterile line with higher sugar content in flower is propitious to attraction for bee visiting, which can increase the rate of effective boll and decrease the rate of aborted seed in result of higher yield of hybrid seed.